Genetic variants associated with skin photosensitivity in a southern European population from Spain. Issue 6 (25th July 2018) - Hernando, Barbara; Sanz‐Page, Elena; Pitarch, Gerard; Mahiques, Laura; Valcuende‐Cavero, Francisca; Martinez‐Cadenas, Conrado
Summary: Background/Purpose: Recent GWAS studies, mostly performed in populations of North European origin, have identified the genetic loci associated with pigmentation, sun sensitivity, freckling and skin cancer susceptibility. Here, we aimed at addressing the genetic determinants of sunlight sensitivity in Spain, a southern European population. Methods: Nine SNPs located in 8 pigmentation‐related genes ( IRF4, TYR, ASP, HERC2, OCA2, BNC2, SLC24A4 and SLC45A2 ) were genotyped in 456 Spaniards. Additionally, the complete sequence of the MC1R gene was obtained, testing each nonsynonymous mutation supported by the classification as R or r alleles. A standardised questionnaire was used to collect demographic characteristics, pigmentation and sun sensitivity traits, as well as sun exposure habits. Results: MC1R R alleles and IRF4 rs12203592 were significantly associated with sunlight sensitivity at the Bonferroni‐corrected level ( P ‐value < 4.54 × 10 −3 ). Genetic variants in SLC45A2 (rs16891982) and HERC2 (rs12913832) were also found to be significantly associated with skin photosensitivity in our Spanish sample. Interaction analysis using the MDR method revealed epistatic effects when these four variants were considered together. Conclusion: MC1R, IRF4, HERC2 and SLC45A2 play a significant role in skin sensitivity to sunlight in the Spanish population. Moreover, interaction among these four loci seems to modulate the ability of the skin to respond to UV radiation.